Empowering farmers through a human-centered advisory approach: Enhanced support yields tangible benefits - Desta, Lulseged Tamene; Mesfin, Tewodros; Degefie, Tibebe; Ebrahim, Mohammed; Abera, Wuletawu; Endrias, Abrhame (2025)
A human-centered, socially inclusive approach to advisory services combines financial support with tailored agronomic advice. Partnering the private sector, LERSHA , we developed integrated solutions that link credit and insurance with advisory services, fostering evidence-based practices. This approach encouraged financial institutions to offer customized agricultural financing, addressing resource-limited farmers’ needs. Collaboration with the Alliance of Bioversity International and the International Center for Tropical Agriculture (the Alliance) enabled data-driven credit scoring for 8,608 farmers across five regions, with 1,450 farmers securing microloans. These efforts empower farmers to adopt improved practices while ensuring financial inclusion.